Evaluation of an assay for methylated BCAT1 and IKZF1 in plasma for detection of colorectal neoplasia - Pedersen, Susanne K.; Symonds, Erin L.; Baker, Rohan T.; Murray, David H.; McEvoy, Aidan; Van Doorn, Sascha C.; Mundt, Marco W.; Cole, Stephen R.; Gopalsamy, Geetha; Mangira, Dileep; LaPointe, Lawrence C.; Dekker, Evelien; et al. (BMC cancer, 2015)
Specific genes, such as BCAT1 and IKZF1, are methylated with high frequency in colorectal cancer (CRC) tissue compared to normal colon tissue specimens. Such DNA may leak into blood and be present as cell-free circulating DNA. We have evaluated the accuracy of a novel blood test for these two markers across the spectrum of benign and neoplastic conditions encountered in the colon and rectum. Circulating DNA was extracted from plasma obtained from volunteers scheduled for colonoscopy for any reason, or for colonic surgery, at Australian and Dutch hospitals. The extracted DNA was bisulphite converted and analysed by methylation specific real-time quantitative PCR (qPCR). A specimen was deemed positive if one or more qPCR replicates were positive for either methylated BCAT1 or IKZF1 DNA. Sensitivity and specificity for CRC were estimated as the primary outcome measures. Plasma samples were collected from 2105 enrolled volunteers (mean age 62 years, 54 % male), including 26 additional samples taken after surgical removal of cancers. The two-marker blood test was run successfully on 2127 samples. The test identified 85 of 129 CRC cases (sensitivity of 66 %, 95 % CI: 57-74). For CRC stages I-IV, respective positivity rates were 38 % (95 % CI: 21-58), 69 % (95 % CI: 53-82), 73 % (95 % CI: 56-85) and 94 % (95 % CI: 70-100). A positive trend was observed between positivity rate and degree of invasiveness. The colonic location of cancer did not influence assay positivity rates. Gender, age, smoking and family history were not significant predictors of marker positivity. Twelve methylation-positive cancer cases with paired pre- and post-surgery plasma showed reduction in methylation signal after surgery, with complete disappearance of signal in 10 subjects. Sensitivity for advanced adenoma (n = 338) was 6 % (95 % CI: 4-9). Specificity was 94 % (95 % CI: 92-95) in all 838 non-neoplastic pathology cases and 95 % (95 % CI: 92-97) in those with no colonic pathology detected (n = 450). The sensitivity for cancer of this two-marker blood test justifies prospective evaluation in a true screening population relative to a proven screening test. Given the high rate of marker disappearance after cancer resection, this blood test might also be useful to monitor tumour recurrence. ACTRN12611000318987 .